The sorrows of an American : a novel - Hustvedt, Siri (Henry Holt and Co., 2008)
When Erik Davidsen and his sister, Inga, find a disturbing note from an unknown woman among their dead father's papers, they believe he may be implicated in a mysterious death. The Sorrows of an American tells the story of the Davidsen family as brother and sister uncover its secrets and unbandage its wounds in the year following their father's funeral.